STRATEGI PENGEMBANGAN DAN BAURAN PEMASARAN POTENSI KOMODITAS KOPI DALAM RANGKA PENGUATAN PASAR PRODUK PERTANIAN SECARA INTEGRATIF DENGAN SEKTOR PARIWISATA DI KABUPATEN BANYUWANGI - Dimas Imaniar; Andhika Wahyudiono (Politeknik Negeri Batam, 2018)
The one of commodities that contribute economies in agricultural sector, has an integrated competitiveness and agribusiness that can improve the welfare of the famers is coffee. This research aims to find out; Formulating development strategy on coffee commodities in order to strengthen agricultural product market in integrative with tourism sector in Banyuwangi Regency. The research area is determined purposively, that is in Banyuwangi Regency. This research uses descriptive and analytic method. Sampling method is conducted purposively (purposive sampling). This research is analyzed using Location Quotient, Marketing Mix and Force Field Analysis tools. The research results show that by formulation of strategy model of development of coffee commodities in order to strengthen agricultural product market in integrative with tourism sector in Banyuwangi Regency which can be used on of the government policy and provide better life expectancy of coffee farmers.